SERVIÇO DE CONVIVÊNCIA E FORTALECIMENTO DE VÍNCULOS PARA PESSOAS IDOSAS: UM ESTUDO NO MUNICÍPIO DE REBOUÇAS-PR - Cabral, Giovana Donaise (2018)
This research aimed to characterize the Service of Coexistence and Strengthening of Links for Elderly People of the municipality of Rebouças-PR from the reports of users and professionals. To do this, we sought to know who are the professionals who work in the service and who are the users who attend the SCFVI, as well as to know the perception of professionals and users about this service and if there is a correlation between the perception of professionals and the users with the current public policies of attention to the elderly. The research is justified by its interdisciplinary content that covers the areas of health, education and care, in order to contribute in consonance with the other related sciences in the generation of information regarding the welfare and social and family integration of the elderly people, and in order to encourage government spheres to promote health maintenance and the active participation of these people in the community. Methodologically, it is characterized as a descriptive and exploratory research with a qualitative approach, having been carried out through a documentary and bibliographic survey using books, electronic sites, documents, legislation, among others, and semi-directed interviews with professionals and users of the service . The total number of participants was 17, with 12 elderly people using the service and five professionals. The analysis of the results was done through content analysis through the thematic-categorial modality. As a conclusion, the SCFVI of the municipality of Rebouças is characterized as an eminently urban service. It is preventive in nature, it is held every two weeks at the headquarters of the CRAS to which it is referenced. It serves a target audience of 15 to 20 elderly people at risk, isolation and / or social vulnerability, with the purpose of strengthening family and community ties, aiming at emancipatory alternatives for the defense and affirmation of rights, development of capacities and potentialities, empowerment of these elderly people, as well as, opportunizing the improvement of the quality of life, through information with lectures by professionals of specific areas, dealing with themes such as health, nutrition, news, rights, among others.